DO GOOD WRITERS SPEAK BETTER? INVESTIGATION OF INDONESIAN EFL STUDENTS’ SPEAKING ABILITY AND WRITING PROFICIENCY ACROSS COMPETENCE LEVELS - Bambang Yudi Cahyono (Siliwangi University, 2017)
This study examined the correlations between Indonesian EFL students’ speaking ability and their writing proficiency at two levels: individually and across competence levels. It involved 74 undergraduate students majoring in English Language Teaching (ELT). They were taking Essay Writing course in the English Department of Universitas Negeri Malang (State University of Malang), East Java. The students were taught to write essays of five types: examplification, comparison/contrast, classification, process analysis, and cause/effect analysis. However, in this study the students’ writing proficiency was measured from the scores of their cause/effect analysis essays in particular. In the teaching and learning process, the students were made aware that they had to complete two tasks: writing a cause/ effect analysis essay on ELT topics and presenting their essays orally by using power point slides in front of the class. The students’ essays and their presentation performances were rated by two raters after some practices to reach agreement in scoring. The results showed that there were positive correlations between Indonesian EFL students’ speaking ability and their writing proficiency both individually or across competence levels. The findings suggest that the higher the students’ writing proficiency scores, the higher their speaking ability scores; and the students’ scores in speaking ability and writing proficiency were consistent across competence levels, meaning that the students who are at the top level remain to be at the top in the two productive skills.